Penerapan Metode Fuzzy Tsukamoto untuk Prediksi Jumlah Produksi Tanaman Cabai - Irmayansyah Irmayansyah; Annisa Nur Rossdiana (Teknois : Jurnal Ilmiah Teknologi Informasi dan Sains, 2021)
Inaccuracy in predicting the amount of chili production is one of the problems found in chili production. Based on the data obtained from observations and interviews conducted with the supervisor of chili plantations, there are 3 variables that can be used to predict the amount of chili production, namely land area, number of seeds, and maintenance costs. The application of the Fuzzy Tsukamoto method to this problem is one of the most appropriate and effective ways. To find out the accuracy of the application of the Tsukamoto fuzzy method for predicting the amount of chili production, it was carried out by comparing the prediction of the amount of chili production obtained from the application of the Fuzzy Tsukamoto method with the actual data on the amount of chili production using the Mean Absoulute Percentage Error (MAPE) formulation, the results obtained were 14%. Can be categorized as a good forecast. The existence of a system for predicting the amount of chili production will be more effective and efficient in its use, the system testing was carried out on 30 users using the Post-study System Usability Quistionnaire (PSSUQ)instrument, it was obtained a value of 80,15% was obtained which can be categorized as feasible to be implemented.